Improving Qur'an Reading Literacy Using Peer Teaching Methods Based on Local Wisdom - Hayati, Ridha Husnul; Azizah, Zahratul; Yusuf, Muhammad; Mulyani, Rila Rahma (Universitas Negeri Padang, 2025)
The literacy level in the art of reading the Qur'an in Nagari Singguliang, Lubuk Alung, remains relatively low, as indicated by the limited number of qari and qari’ah who can perform during religious events. This community service program aims to enhance Qur'anic reading literacy through a Peer Teaching method based on local content implemented at Surau Nurul Jama'ah. The activities involved peer mentoring, Qur’an recitation practice, and training in tajwid and tarannum using locally contextualized learning materials. The “Back to Surau” program was also conducted to revitalize the surau as a center of religious and community learning. The results showed a significant increase in participants’ ability to recite the Qur’an melodiously, as well as greater engagement in religious activities among youth and adults. Additionally, community involvement in surau programs strengthened local Islamic identity and fostered sustainable religious literacy.